Distribution of Constituents and Metabolites of Maritime Pine Bark Extract (Pycnogenol(®)) into Serum, Blood Cells, and Synovial Fluid of Patients with Severe Osteoarthritis: A Randomized Controlled Trial - Mülek, Melanie (Nutrients, 2017)
The present randomized controlled study aimed to investigate the in vivo distribution of constituents or metabolites of the standardized maritime pine bark extract Pycnogenol(®). Thirty-three patients with severe osteoarthritis scheduled for a knee arthroplasty were randomized to receive either 200 mg per day Pycnogenol(®) (P+) or no treatment (Co) over three weeks before surgery. Serum, blood cells, and synovial fluid samples were analyzed using liquid chromatography coupled to tandem mass spectrometry with electrospray ionization (LC-ESI/MS/MS). Considerable interindividual differences were observed indicating pronounced variability of the polyphenol pharmacokinetics. Notably, the highest polyphenol concentrations were not detected in serum. Catechin and taxifolin primarily resided within the blood cells while the microbial catechin metabolite δ-(3,4-dihydroxy-phenyl)-γ-valerolactone, ferulic, and caffeic acid were mainly present in synovial fluid samples. Taxifolin was detected in serum and synovial fluid exclusively in the P+ group. Likewise, no ferulic acid was found in serum samples of the Co group. Calculating ratios of analyte distribution in individual patients revealed a simultaneous presence of some polyphenols in serum, blood cells, and/or synovial fluid only in the P+ group. This is the first evidence that polyphenols distribute into the synovial fluid of patients with osteoarthritis which supports rationalizing the results of clinical efficacy studies.